The Relations Between Ottoman State and Egypt (1863 - 1879) - نبراس خليل ابراهيم ايمان عبد الله حمود (College of Education for Women, 2019)
Facts and information contained showing in axes Find Egyptian Ottoman relations (1863-1879), has gone through stages varying between tides, has witnessed the Khedive Ismail three sultans Ottomans were Abdul Aziz Murad V, Abdul Hamid II, and since the Khedive Ismail to judge sought to expand independence Egypt access to many privileges of the sovereign on Egypt Ottoman Empire, in order to reach the country to independence, has been chosen by the payment of money and gifts to gain independence, without resorting to arms, and from this point of Khedive make a lot of money to get the privileges, the state of the Ottoman were not to issue Farmans but against the huge amounts of money, and as a result of that policy got Furman in 1866, under which justice and inherit the throne system, and Furman in private in 1867 by granting the title of Khedive, but the efforts of the Khedive Ismail to show the appearance of the independent King was a cause of the Egyptian Ottoman crisis between 1869 and 1872 is that the Khedive Ismail ambitions that one has made him seek to get closer to the government of Astana for more than Farmans, that managed to get a firman Whole in 1873, and which culminated in pursuit of the Khedive to gain full independence, the culmination of a final, and made under its association with the Ottoman state as it were non-existent.It is clear from Farmans obtained by Khedive Ismail of Egypt to link the Ottoman state became nominally, is no longer the Ottoman state the right to intervene in and appoint to Egypt, as well as Egypt's independence in economic terms from the Ottoman Empire. On the other hand, the Khedive Ismail policy wrong and borrowed huge amounts of money from foreign banks, European countries pushed for intervention in the affairs of Egypt during his reign, until it came out that those countries have begun fear of non-payment of debts, so pressed by Britain and France at the Porte to isolate Alkhdioa Ismail was to do so in the twenty-sixth of June 1879